Chemical and Nutritional Composition of Selected Legumes Available in Kebbi State Nigeria - Fakai, Rufai Usman; Aliyu Garba (MultiTech Publisher, 2023)
Legumes are important source of high-quality protein and oil, as well as other nutritious substances. The higher the content of these nutritious substances in a given legume the higher it’s quality. The mineral and proximate contents of the variety of legumes available in Mahuta town, were determined using standard procedures. The results showed that legume samples vary significantly (p < 0.05) in the chemical parameters evaluated. Soy beans and Ground nut had significantly high concentration of protein than Bambara nut. Equally, Bambara nut and Ground nut shows superiority in carbohydrate composition. Soy bean and Ground nut showed significantly higher concentration of mineral and abundance, while bambaranut had the lowest mineral and lipid contents. Hence, the selected legumes evaluated can serve as alternative protein sources with carbohydrate good minerals, and fibre.